2016
DOI: 10.1016/j.reprotox.2016.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 4-nonylphenol on spermatogenesis and induction of testicular apoptosis through oxidative stress-related pathways

Abstract: This study tested the hypothesis that prepubertal exposure to 4-nonylphenol (NP) affects reproductive function in male rats. Twenty-four rats at five-weeks-old were randomly divided into four groups and treated with NP at varying concentrations (0, 5, 20, and 60mg/kg/2d) for thirty days by intra-peritoneal injection. 60mg/kg NP induced spermatogenic degeneration and pronounced deficits in epididymal sperm count, motility and function, whereas potentially stimulatory effects were observed at 5 NPmg/kg. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 60 publications
4
41
0
Order By: Relevance
“…It is widely accepted that FasL expressed on Sertoli cells can initiate apoptosis in neighbouring germ cells that express Fas (Lee, Richburg, Shipp, Meistrich, & Boekelheide, ). The Fas/FasL system activates caspase‐8 and its downstream caspases such as caspase‐3 triggering programmed cell death (Huang et al., ).The activation of the Fas/FasL system by the varicocele may therefore have an important role in the apoptosis of both Sertoli cells and germ cells because our results demonstrated that the expression of Fas, FasL and caspase‐3 increased in response to the establishment of a varicocele, consentient with results of many other studies (Duan et al., ; Huang et al., ). As secretion of inhibin B involves both Sertoli cells and germ cells (Meachem et al., ), the activation of the Fas/FasL system in response to the presence of the varicocele would lead to apoptosis of both Sertoli cells and germ cells and consequently a decrease in inhibin B secretion.…”
Section: Discussionsupporting
confidence: 90%
“…It is widely accepted that FasL expressed on Sertoli cells can initiate apoptosis in neighbouring germ cells that express Fas (Lee, Richburg, Shipp, Meistrich, & Boekelheide, ). The Fas/FasL system activates caspase‐8 and its downstream caspases such as caspase‐3 triggering programmed cell death (Huang et al., ).The activation of the Fas/FasL system by the varicocele may therefore have an important role in the apoptosis of both Sertoli cells and germ cells because our results demonstrated that the expression of Fas, FasL and caspase‐3 increased in response to the establishment of a varicocele, consentient with results of many other studies (Duan et al., ; Huang et al., ). As secretion of inhibin B involves both Sertoli cells and germ cells (Meachem et al., ), the activation of the Fas/FasL system in response to the presence of the varicocele would lead to apoptosis of both Sertoli cells and germ cells and consequently a decrease in inhibin B secretion.…”
Section: Discussionsupporting
confidence: 90%
“…NP has been found in various human tissues (Deng et al, 2010;Asimakopoulos et al, 2012) and to cause a wide range of reproductive and developmental toxicities in fish and mammals (Chapin et al, 1999;El-Sayed Ali et al, 2014;Duan et al, 2016a;Duan et al, 2017b). Male reproductive system toxicity is one of the prominent adverse effects of NP (Noorimotlagh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence that NP could exert estrogenic actions and disturb hormonal homeostasis has arisen from studies in male rats models (Chapin et al, 1999;Duan et al, 2017a). Our previous studies found that pre-pubertal exposure to NP in rats induced reproductive dysfunction during adulthood (Duan et al, 2016a;Huang et al, 2016). NP treatment affects spermatogenesis, sperm function and morphology (El-Sayed Ali et al, 2014;Cheng et al, 2017;Duan et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, our previous study outlined that NP treatment triggers Sertoli cell (SC) autophagy, probably through the ROS-mediated AMPK-mTOR pathway (Duan et al 2016c). Additionally, NP exposure is shown to increase oxidative stress and germ cell apoptosis in testis, to cause seminiferous tubule degeneration and to reduce hormone secretion, consequently impairing sperm parameters, capacitation and morphology (Duan et al 2016a;Duan et al 2016b;Lu et al 2014;McClusky et al 2007). Although increasing evidence suggests that autophagy activity may play an important function in the pathogenesis of male reproductive toxicity (Han et al 2015), no information regarding NP effects on autophagy induction in vivo is currently available.…”
Section: Introductionmentioning
confidence: 99%